Robert Helyer Thayer papers - Thayer, Robert Helyer, 1901-1984.
Correspondence, memoranda, legal briefs and case files, reports, financial records, scrapbook, printed matter, maps, photographs and other papers documenting Thayer's service as assistant secretary for cultural and educational affairs at the U.S. State Dept., assistant ambassador to France and minister to Romania, district attorney for New York County, and in the U.S. Naval Reserve providing combat intelligence during World War II. Also documents his work as assistant counsel to Charles A. Lindbergh on the Lindbergh kidnapping case, private law practice in New York City, and political activities in the Republican Party. Subjects include American and Canadian bankruptcy laws; Thayer's support of Thomas E. Dewey's campaigns for New York City, New York state, and national offices; Unesco; and art in U.S. embassies. Correspondents include McGeorge Bundy, William R. Castle, Thomas E. Dewey, C. Douglas Dillon, William J. Donovan, Allen Welsh Dulles, John Foster Dulles, Sol Hurok, Dean Rusk, and Sinclair Weeks.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Diplomat, lawyer, and New York public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bundy, McGeorge -- Correspondence; Castle, William R. -- 1878-1963 -- Correspondence; Dewey, Thomas E. -- 1902-1971 -- Correspondence; Dillon, C. Douglas -- 1909-2003 -- Correspondence; Donovan, William J. -- 1883-1959 -- Correspondence; Dulles, Allen, -- 1893-1969 -- Correspondence; Dulles, John Foster, -- 1888-1959 -- Correspondence; Hurok, Sol, -- 1888-1974 -- Correspondence; Lindbergh, Charles A. -- 1902-1974.; Lindbergh, Charles Augustus, -- 1930-1932 -- Kidnapping, 1932.; Rusk, Dean, -- 1909-1994 -- Correspondence; Weeks, Sinclair, -- 1893-1972 -- Correspondence; United States. -- Assistant Secretary of State for Educational and Cultural Affairs; United States. -- Department of State; United States. -- Naval Reserve; Republican Party (U.S. : 1854- ); Unesco; Art; Congresses and conventions; Embassy buildings; Diplomatic and consular service, American; Bankruptcy -- Canada; Bankruptcy -- United States; Kidnapping -- United States; Law -- New York (State) -- New York County; Practice of law -- New York (State) -- New York; Public prosecutors -- New York (State) -- New York County; World War, 1939-1945 -- Military intelligence; France -- Foreign relations -- United States; New York (N.Y.) -- Politics and government; New York (State) -- Politics and government -- 20th century; Romania -- Foreign relations -- United States; United States -- Foreign relations -- France; United States -- Foreign relations -- Romania; United States -- Politics and government -- 20th century; Diplomats; Lawyers; Public officials -- New York (State)